STRATEGI PENGEMBANGAN DAYA TARIK WISATA PANTAI MUTIARA INDAH UNTUK MENINGKATKAN KUNJUNGAN WISATA DI MUARA BADAK KABUPATEN KUTAI KARTANEGARA - Melita Dwi Yana, (Jurnal Cakrawala Ilmiah, 2022)
Nature Tourism is a tourist attraction that is developed more based on the grace of beauty and uniqueness that is available in nature such as beaches, seas, lakes, mountains, forests, rivers, and waterfalls. Muara Badak District has a natural tourist attraction, namely Mutiara Indah beach tourism which is located in Pangempang Village, Muara Badak District. The purpose of this research is to find out and identify how the strategy of developing Mutiara Indah beach tourist attraction is to increase tourist visits in Muara Badak and what are the inhibiting factors faced by Mutiara Indah beach managers. In this study using the theory of Tourism Development by Suryadana (2015). The research method used is direct interviews with Key Informants and Informants, where this type of research is a qualitative type. The research location is Mutiara Indah Beach, which is located in Pangempang Village, Muara Badak District, Kutai Kartanegara Regency. The conclusion in this study is that Accessibilities to Mutiara Indah Beach are appropriate because there are road directions but there is still no public transportation to Mutiara Indah beach, amenities are appropriate because facilities such as gazebos and toilets are available, attractions are appropriate because there is a photo stand provided by the manager. and hospitality is appropriate because the surrounding community is friendly and willing to mingle with visitors to Mutiara Indah Beach. To develop Mutiara Indah beach, the manager is expected to work with the Tourism Office and also work with companies to improve existing facilities at Mutiara Indah Beach, Muara Badak District.